An Irish provenance for the Monzie Estate gold? - Ó Néill, John (Proceedings of the Society of Antiquaries of Scotland, 2009)
General Alexander Campbell of Monzie, a little known antiquarian, provides the link between group of gold objects now held by the National Museum of Scotland and purporting to come from the Monzie Estate, and, a possible Irish provenance. Known objects in Campbell’s possession include several finds from Ireland and at least one book on Irish antiquities whilst his military career took him to Ireland on a number of occasions in the late 18th and early 19th century. Many Irish collectors from this period are known through later acquisitions by public museums. Individuals like Campbell who were based outside of Ireland are not as well known and the true extent of their collecting is uncertain and is perhaps now unmappable but does raise the possibility that a larger quantity of Irish material was moved to collections in Scotland than is generally assumed.